Revitalising Organisational Performance: Innovative Strategies for Information Technology-Based Human Resource Development - Kraugusteeliana Kraugusteeliana; Silvy Sondari Gadzali; Abu Muna Almaududi Ausat (Politeknik Ganesha Medan, 2023)
In the rapidly evolving era of globalization and digitization, organizations are confronted with swiftly developing challenges. Human resource management (HRM) emerges as a primary key in responding to these dynamics, with employee development serving as a crucial focus to ensure organizational competitiveness and sustained performance. This research aims to investigate and develop innovative strategies in HRM based on information technology (IT), with a specific focus on enhancing organizational performance. The study employs an extensive review of existing literature utilizing qualitative analysis to obtain a comprehensive understanding of the subject, spanning the period from 2012 to 2023. The study's findings indicate that the revitalization of organizational performance through innovative strategies in IT-based human resource development marks a significant step in facing contemporary business challenges. The integration of information technology not only enhances the efficiency of employee training and development but also enables organizations to make smarter decisions based on real-time data analysis. Various technologies such as virtual reality, artificial intelligence, and collaborative tools create a new landscape for human resource management, fostering a culture of continuous learning and enhancing organizational creativity and resilience.